Sosialisasi Etika Digital Penggunaan Gadget untuk Pencegahan Bulliying pada Siswa SDN Tambibendo 2 Kediri - Ahsin, Nurul; Nur Afifah, Lailatul; Avifah, Nur; Lathifatul Mufidah, Ulfah; Farah Sabila, Lana; Jalaludin Akbar, Achmad (Bakti Insani: Jurnal Pengabdian dan Pemberdayaan, 2025)
The Community Service Program conducted by KKN Group 19 at SDN Tambibendo 2 Kediri aimed to enhance students’ understanding of digital ethics and prevent bullying, particularly cyberbullying. This program was motivated by the increasing use of gadgets among children, which is not yet balanced with adequate digital literacy and therefore poses risks of negative behaviors in online interactions. The activities were carried out using interactive methods, including lectures, educational video screenings, case simulations, games, and ice-breaking sessions to encourage active student participation. The results indicated an improvement in students’ digital literacy, increased awareness of the impacts of bullying, and the development of respectful attitudes in digital interactions. These findings highlight the crucial role of teachers, parents, and schools in supervising and guiding children’s gadget use to prevent cyberbullying behaviors.